MO572BONE BIOPSY AND MINERAL METABOLISM, CARDIOVASCULAR DISEASE AND PATIENT SURVIVAL IN END-STAGE RENAL PATIENTS. (29th May 2021) - Ferreira, Ana Carina; Cotovio, Patrícia; Aires, Inês; Mendes, Marco; Navarro, David; Silva, Cecília; Caeiro, Fernando; Salvador, Rute; Correia, Bruna; Cabral, Guadalupe; Nolasco, Fernando; Ferreira, Manuel Anibal A
Abstract: Background and Aims: Chronic kidney disease-mineral and bone disorder (CKD-MBD) is frequent in end-stage renal disease (ESRD) patients, increasing morbid-mortality. The aim of this study was to determine the prevalence and phenotype of bone disease before transplantation; and to correlate FGF23, klotho and sclerostin serum levels with bone histomorphometric parameters and CV disease. The secondary aim was to correlate bone biopsies data with other bone related parameters, as PTH, bone alkaline phosphatase, 25-hidroxivitamin D3, calcitonin, calcium, phosphorus, and magnesium. Method: We performed a prospective cohort study of a sample of ESRD patients listed for renal transplant. All patients were submitted to renal transplant and were followed for 12 months. Patient and graft survival were recorded. At inclusion, demographic and clinical data were collected, laboratorial evaluation; bone biopsy and X-ray of the pelvis and hands (Adragão score) were performed. Continuous variables are presented as medians and categorical variables as frequencies. Associations between variables were performed using Wilcoxon rank sum test, Fisher and Kruskal Wallis test. Multivariate analysis was performed using logistic regression. STATA software was used and p < 0.05 was considered statistically significant. Results: We included 84 patients. Median age 53.5 (IQ range: 40.5 – 61.5) years, 59 men (70.2%), 65 caucasian (77.4%). The median left ventricular mass index was 108.5 (92 – 129) g/m2, with 32 patients presenting left ventricular hypertrophy and 19 valve calcifications. Median Adragão score was 1 (0 – 2). We diagnosed adynamic bone disease in 15 patients; hyperparathyroid bone disease in 19 patients; osteomalacia in 1 patient and mixed renal osteodystrophy in 3 patients. At the end of 12 months, 4 patients died, 5 had graft failure (non-primary function) and 4 had a cardiovascular event. Sclerostin was found to be a risk factor for low bone volume; whereas low phosphorus, low FGF23 and high bAP risk factors for abnormal mineralization. High turnover was mainly present in patients with high bAP and phosphorus and low sclerostin levels. The presence of valve calcifications was associated with low volume and with low or high turnover disorder. FGF23 appears as an important independent factor for vascular calcifications [as well age (p=0.009), BMI (p=0.02), presence of diabetes (p=0.01)], and for cardiovascular events. Sclerostin emerged as a risk factor for vascular calcifications and lower levels of sclerostin were associated with patient survival at the end of 12 months. Conclusion: From the bone-derived hormones, sclerostin and FGF23 seem to act as risk factors for vascular calcifications and worse outcomes.